Pengembangan Model Tata Kelola Keuangan PAUD Berbasis Integrasi Good Financial Governance - Febryanggita Kusuma Pranata; Annisa Dwi Nursanti; Fetty Ernawati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The financial management of Early Childhood Education (PAUD) institutions in Indonesia still faces recurring structural problems, including disorderly financial record-keeping, weak budget planning, low transparency and accountability, and limited human resource capacity in financial management. These conditions directly impact the sustainability and quality of early childhood education services. Although some PAUD institutions have implemented certain elements of governance, these practices are carried out separately and have not been integrated into a systematic cycle. This study aims to develop a financial governance model for PAUD based on the integration of Good Financial Governance principles, encompassing transparency, accountability, effectiveness, efficiency, and integrated budget planning. The research employs a qualitative approach with a library study method through thematic content analysis of scientific literature published between 2017 and 2026, sourced from Google Scholar, SINTA, and GARUDA databases. The study results in a conceptual model operationalized through an input–process–output approach with five interconnected stages: participatory budget planning based on digital platforms, budget implementation via an e-approval system, integrated financial recording, communicative financial reporting, and data-based monitoring and evaluation. All stages are reinforced by the use of digital technology as a supporting instrument for transparency and accountability. This model theoretically contributes to enriching educational management studies through a more comprehensive integrative framework and practically serves as an implementation reference for PAUD managers and a basis for developing more systematic regulations to effectively, efficiently, and sustainably improve the quality of financial governance in PAUD institutions.